Effects of Gravel Percentage to Compaction Density and Stability of Embankment - Sukmawati, Eka; Solin, Dian Purnamawati; Farichah, Himatul (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2024)
Embankments are frequently used in the construction of road, railway, airport, dams and other types infrastructure. Soil compaction is a crucial part of the construction process of embankment. Thus, soil compaction needs to be conducted and investigated in such a way so embankment will not experience large settlement that could lead to collapse. Generally, soil compaction density testing is performed using the sand cone method according to ASTM D-1556. The material used in this test is not carefully considered, which may lead to inaccurate results. In this study, the sand cone correction test according to ASTM D-4718 which consider the percentage of gravel is established to identify the compaction density of embankment and the effect to its stability. 16 secondary data of compaction density have been collected from the construction of embankment. According to the data, the compaction density of the embankment has met the specifications. The relationship between the gravel percentage and the compaction density is obtained. With a determination coefficient (R2) value of 0.805, it can be understood that these two variables have a highly significant correlation. Furthermore, to understand the relationship between the compaction density and the stability of the embankment, a slope stability analysis was conducted on the embankment using the Fellenius method. The result shows that when the compaction density of the embankment meet the specifications, embankment is stable with the safety factor (SF) of 1.511. Furthermore, both variables have a very strong relationship. The safety factor of the embankment is increased as the compaction density increases.